Penerapan Rendam Air Kencur Hangat Pada Kaki Untuk Mengurangi Edema Fisiologis Pada Asuhan Keperawatan Ibu hamil Di Puskesmas Kayamanya: Application of Warm Kencur Water Soak on Feet to Reduce Physiological Edema in Nursing Care for Pregnant Women at Kayamanya Health Center - Siti Nafra; Dafrosia Darmi Manggasa (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Introduction : Pregnancy is the period that starts from conception to the birth of the fetus. During the pregnancy process, physical changes occur in pregnant women, one of which is physiological leg edema. So that one of the interventions that needs to be done in reducing physiological edema is by doing warm kencur water immersion therapy. The purpose of this study was to describe nursing care for pregnant women by applying warm kencur water immersion to reduce physiological edema at the Kayamanya Health Center. Method : The research method is using a descriptive research method with a case study approach of 1 third trimester pregnant woman patient with a characteristic of experiencing physiological leg edema and no pregnancy complications. Result : Research results Mrs. J complained of swelling in both legs, Mrs. J said that his legs often felt cramps, he often urinated and felt pain in his back area. Mrs. J often feels tired especially if he stands for too long. Mrs. J said he wanted to have a normal delivery, Mrs. J also always received support, motivation from her husband and family in facing childbirth. Nursing problems of discomfort, fatigue, and readiness for childbirth. The interventions were foot bath therapy, positioning, relaxation therapy, pregnancy care education, energy management, activity/rest education, and childbirth education. Implementation carried out for 5 days. Evaluation after implementation that the application of warm kencur water immersion can reduce physiological leg edema in third trimester pregnant women with decreased edema results, the patient appears more relaxed and comfortable, the patient is able to adapt to fatigue, the patient already understands about the delivery that will be faced. Conculsion : The conclusion that the application of warm kencur water soak is very effective in reducing leg edema. Suggestions that patients can do warm kencur water soak therapy independently according to what is taught by researchers